2009
DOI: 10.1068/a41246
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry and Asymmetry in Working and Commuting Arrangements between Partners in the Netherlands: Does the Residential Context Matter?

Abstract: This is the author's Post-print version (final draft post-refereeing as accepted for publication by the journal). The definitive, peer-reviewed and edited version of thisAbstract. Time spent on work and commuting within dual earner households is often analysed separately for individuals, but this does no justice to the reality of dual earner households where decisions on work and commuting are made in a household context. This article reports on a quantitative study of the impact of the residential context on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Finally, geographers have highlighted the importance of space , as the gender division of household labour is more balanced in urban, higher‐density locations, at least in north‐western Europe (Ettema et al . ; De Meester and Van Ham ). Whilst this difference may follow from more egalitarian attitudes about gender roles (Karsten ), it also reflects variations in accessibility and space–time constraints among urban households (Ettema et al .…”
Section: Study Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, geographers have highlighted the importance of space , as the gender division of household labour is more balanced in urban, higher‐density locations, at least in north‐western Europe (Ettema et al . ; De Meester and Van Ham ). Whilst this difference may follow from more egalitarian attitudes about gender roles (Karsten ), it also reflects variations in accessibility and space–time constraints among urban households (Ettema et al .…”
Section: Study Backgroundmentioning
confidence: 99%
“…A third factor is the household situation as reflected in the presence, number and age of children (Bianchi et al . ; Presser ); it has been suggested that in households with one or more young children the division of domestic labour is particularly unequal (De Meester and Van Ham ). Fourth, differences in the degree to which men and women hold egalitarian attitudes toward gender roles have been shown to explain differences in the gender division of domestic responsibilities across households (Huber and Spitze ; Ettema and Van der Lippe ).…”
Section: Study Backgroundmentioning
confidence: 99%
“…A study from the Netherlands found that living in urban areas (densely populated) offered enhanced opportunities, especially for women, to work in combination with other mandatory and leisure activities (Ettema et al 2007) Another study from the Netherlands concluded that it was likely households in highly urbanized areas had working arrangements where both partners worked full time (Meester and Ham 2009). An interpretation was that there were more egalitarian attitudes towards task division between partners in large urban areas.…”
Section: Differences In Commuting Are Related To Multiple Factorsmentioning
confidence: 99%
“…This apparently simple formulation remains vital in understanding why some people will advance more rapidly than others in occupational terms, since it follows that those with credentials and a willingness to move will achieve occupational mobility more quickly than those who are either rooted in place or facing personal constraints on their mobility. Married couples with children and home owners provide obvious examples here [19][20][21]. It is important to note here that it is likely that people who are motivated Urban Studies Research 3 to do better in their careers are also more likely to accept jobs outside their own labour market and therefore requiring longer distance moves.…”
Section: Labour Markets and Escalatormentioning
confidence: 99%